Taxonomic and nomenclatural notes in Microchilus longicornu (Goodyerinae Orchidaceae) - Engels, Mathias E.; C. Smidt, Eric (Phytotaxa, 2022)
Along with the study of Goodyerinae from Brazil and the examination of type material associated with new collections and fresh material, the delimitation and circumscription of Microchilus longicornu, species that have been mistakenly treated as a synonym of M. foliosa, are discussed. Additionally, we present nomenclatural comments with the second phase of the lectotypification of M. longicornu.